Cenozoic Dextral Shearing Along the Arusan Sector of the Great Kavir–Doruneh Fault System (Central Iran). Issue 11 (29th October 2021) - Zanchi, Andrea; Zanchetta, Stefano; Berra, Fabrizio; Mattei, Massimo; Javadi, Hamid Reza; Montemagni, Chiara
Abstract: The structural analysis of large intracontinental wrench faults is fundamental for deciphering the long‐term evolution of continental crust in complex areas in terms of their geodynamic evolution and large‐scale crustal block displacements. In this contribution, we demonstrate a pre‐Miocene dextral activity of the present‐day left‐lateral Great Kavir ‐ Doruneh Fault System (GKDFS, Central Iran), one of the major intracontinental active strike‐slip faults extending from the Afghan border to the Nain region between Central Iran and the Sanandaj‐Sirjan Zone. We document important dextral shearing recorded along a segment of the GKDFS, the Arusan Fault System (AFS), located east of Jandaq, close to the present‐day active trace of the GKDFS. The AFS include several ENE‐WSW striking strands exposed for a length of more than 50 km, which couple pre‐Cretaceous ophiolites and metamorphic basement units with the Cretaceous succession of the Khur basin. The fault shows transpressional structures consistent with a dextral shear including thrusts and en échelon folds affecting the Cretaceous carbonate units. Paleostress reconstruction based on mesoscopic fault analysis and related folds geometry allowed to establish vorticity parameters indicating that deformation occurred close to a total simple shear regime with a calculated Wk between 0.9 and 1. The enormous Meso‐Cenozoic dextral displacements occurred along the AFS and along the entire GKDFS are attested by the up to several hundreds of kilometers offset of the Paleotethys suture zone, from NE Iran to the western border of Central Iran. Key Points: The Great Kavir‐Doruneh Fault System (GKDFS) is an active intracontinental left‐lateral shear zone extending several hundreds of km The Arusan Fault System (AFS) is part of the GKDFS. Dextral kinematic of the AFS indicate that also GKDFS was dextral before Late Miocene The Cretaceous to Miocene dextral GKDFS accounts for the more than 500 km displacement of the Paleotethetys suture from NE to Central Iran